SPARX-R computerized therapy among adolescents in youth offenders' program: Step-wise cohort study - Theresa M. Fleming; Bridgette Gillham; Lynda M. Bavin; Karolina Stasiak; Sonia Lewycka; Julie Moore; Matthew Shepherd; Sally Nicola Merry (Internet Interventions, 2019)
Background: Youth offenders have high rates of unmet mental health needs, including elevated rates of subclinical or clinical depression. Computerized cognitive behavioral therapy (cCBT) has been shown to be effective for depression, and cognitive behavioral therapy (CBT) is among the most effective psychological treatments for offence related behaviours. We planned to evaluate the impact of SPARX-R 1.0 (the first iteration of a revised version of SPARX cCBT) for adolescents in a community day program (Mentoring Youth New Directions or MYND) for male recidivist youth aged between 14 and 17 years. Recruitment and retention in the trial were lower than anticipated. In this brief report we present main findings and discuss implications. Methods: We developed a stepwise cohort design to investigate the acceptability and effectiveness of SPARX-R in a complex, real-world setting. Participants were allocated to the MYND program only (treatment as usual), or MYND with the addition of SPARX-R. All adolescents referred to MYND within a specified period were assigned to one of four social workers, as per usual practice. Each social worker was randomized to begin SPARX-R with consenting new clients from one of four time points. Assessments were completed within the first two weeks of commencing the MYND program and then at 10 and 20 weeks after commencement. We solicited brief feedback on SPARX-R from young people and staff who used it. Results: Of 64 eligible youth who began MYND during the trial period, 51 consented but 25 stopped attending MYND despite court orders or because their court orders were changed. Nineteen participants were randomized to SPARX-R but only two completed two or more levels of the 7-level program, so it was not possible to evaluate the impact as planned. The four participants who provided feedback were indifferent or negative about SPARX-R. Staff advised that technical difficulties (such as loading or saving problems) were off putting and that SPARX-R was slow and not appealing to their clients. Conclusions: Computerized CBT was not successfully implemented in this group, highlighting challenges in retention in this non-residential justice program. The findings also indicate that computerized therapies of proven acceptability and effectiveness in one setting may be unappealing in another. Implementation and equity efforts need to consider and test the specialist needs of diverse groups.